How Education Subsidies Affect Junior High School Students’ Noncognitive Ability Development: Evidence from China - Yimin Zheng; Yifan Zheng; Xinqiao Liu (Education Sciences)
Education subsidies play a crucial role in allocating educational resources and significantly impact students’ ability development. This study utilizes data from the China Education Panel Survey to examine the effects of education subsidies on junior high school students’ ability development, employing the framework of new human capital theory along with least squares, propensity score matching, and quantile regression models. The findings reveal that, first, education subsidies exert a significant positive effect on students’ noncognitive abilities, although no similar effect is observed for their cognitive abilities. Second, education subsidies exhibit a “compensatory effect” in enhancing noncognitive abilities, with a more pronounced impact observed among students with lower levels of noncognitive ability. Third, education subsidies particularly benefit female students, students from less affluent families, and those residing in rural areas, with these groups experiencing greater improvements in noncognitive abilities. The study suggests refining education subsidy policies and implementation strategies to foster a collaborative system among families, schools, and society, thereby promoting junior high school students’ comprehensive development through multiple avenues.